PENGURANGAN REJECT DAN PENINGKATAN KELUARAN PRODUKSI HARIAN DENGAN MEMODIFIKASI CHUCK COLLECT PADA MESIN CNC TURNING GOODWAY GLS 150 - Qomarotun Nurlaila; Agus Umar Ryadin; Fajar Hari Yanto (SIGMA TEKNIKA, 2022)
Products 3D35 produced by PT. Team Metal Indonesia uses CNC machines, through two main processes, roughing process and finishing process.  The main problem faced is reject due to the remnants of the piece (chips). Chips stick to the 1 mm chuck collect gap, causing the product 3D35 not to be perfectly attached to the chuck collect, which is tilted or not in the middle position. To solve this problem, it is necessary to modify the chuck collect, by adding a gap with a width of 10 mm and a depth of 10 mm in 6 positions (one axis with the original design, a gap of 1 mm). The modifications are effective for increasing daily production output and reducing rejects in roughing process and finishing process. At roughing process, daily production output increased by 6% (31 pieces/536 pieces) and rejects decreased by 2.6% (from 4.7% to 2.1%). At finishing process, the daily production output increased by 7% (24 pieces / 342 pieces) and the reject was reduced by 1.6% (from 4.3% to 2.7%). This modification can be applied to all chuck collects used to produce product 3D35 and can also be evaluated on other similar products.